61. Stimulated single-fiber electromyography of the frontal muscle: Normative data using concentric needle. Issue 12 (December 2017) - Bastianelli, M.; Lanzo, G.; Cecchini, L.; Scarpino, M.; Spalletti, M.; Lolli, F.; Carrai, R.; Amantini, A.; Grippo, A.
Abstract : To obtain normative values we performed in healthy volunteers (HV) stimulated single-fiber electromyography (SFEMG) of the Frontal muscle using concentric needle electrode (CNE). Frontal muscles SFEMG, after stimulation with needle electrodes of the temporal branch of facial nerve, was conducted in 16 HV (6 males, mean age 43.1, range 20–60 years). Filter settings were 1000 Hz to 10 kHz.The mean consecutive difference (MCD) of the individual fiber and the mean MCD per study were determined. Using the 95% percentile the upper normal limit for the individual fibers of jitter and the mean MCD per study in the HV was 37 μ s and 27 μ s respectively. Having defined these limits, we evaluated 7 patients affected by seronegative Ocular Myasthenia gravis. All these patients showed mean MCD >27 μ s and >2 individual fiber Jitter >37 μ s. The 95% prediction limit might be optimal cut-off value, depending on the clinical question. The obtained reference values were narrow than those reported previously using concentric needles. Stimulation jitter recordings with CNE could be used in practice but borderline findings should be carefully assessed in a prospective study in which consecutive patients with clinical suspicion of Myasthenia Gravis will be enrolled.